Lowest observed surface and weld losses in fused silica fibres for gravitational wave detectors. (10th September 2020) - Cumming, A V; Sorazu, B; Daw, E; Hammond, G D; Hough, J; Jones, R; Martin, I W; Rowan, S; Strain, K A; Williams, D
Abstract: High purity fused silica has become the cornerstone choice for use in the final monolithic stage of the mirror suspensions in the gravitational wave observatories Advanced LIGO (aLIGO) and Advanced Virgo (AdV). The ultra-low thermal noise contributed by these suspensions is one of the key improvements that permitted the Nobel prize winning first direct measurement of gravitational waves in 2015. This paper outlines the first in situ study undertaken to analyse the thermal noise of the final monolithic stage of the aLIGO Hanford detector mirror suspensions. We analysed short operational periods of this detector, when high excitation of the transverse 'violin' modes of the silica suspension fibres occurred. This allowed detailed measurements of the Q -factor of violin modes up to order 8 of individual fibres on separate masses. We demonstrate the highest silica fibre violin mode Q -factors yet measured of up to 2 × 10 9 . From finite element modelling, the dominant surface and weld losses have been calculated to be a factor of 3 to 4 better than previously accepted, and as a result, we demonstrate that the level of noise in the aLIGO final stage silica suspensions is around 30%–40% better than previously estimated between frequencies of 10–500 Hz. This leads to an increase in the estimated event rate by a factor of 2 for aLIGO, if suspension thermal noise became the main limitation to the sensitivity of the detector.